Tramas do cotidiano: religião, política, guerra e negócios no Grão-Pará do setecentos - um estudo sobre a Companhia de Jesus e a política pombalina - Souza Junior, José Alves de (2009)
This work aims to investigate the daily webs of Grao Para in the years of the seven hundreds, in order to try to understand the practices of several social actors, such as the Indians, the Jesuits, the settlers, the colonial authorities, the negros, the mixed race, and the white poor men, before and after Pombal s intervention in the colonizing process of the North Region of Portuguese Brazil. Such practices included religion, politics, war, and business. They developed in a historical context of a strong fight between missionaries and settlers, to control of the Indian workers, which led to an Indian legislation that changed according to the interests in dispute, and to each contender s power beyond the metropolis. The arrival of Sebastião José de Carvalho e Melo, who later became the Marquis of Pombal, at the State Office for Foreign Business and War, resulted in remarkable changes in the politics of the Portuguese colony in the amazon region, which conflicted with the saving plans of the Jesus Company, causing its banishing from Portugal and all of its domains. Explaining this fact required an inquiry into the Jesuit political thinking, in order to show how it conflicted with D. Jose I s intention to settle absolutism, and laicize the Portuguese State. It also required examining issues concerning the relations between the Jesuits and the Governor of the State of Grao Para and Maranhao, Francisco Xavier de Mendonça Furtado, who built and executed the new colonial politics. The banishing of the Jesuits from the Grao Para led to confiscating their belongings, which made it possible both to reconstruct the patrimony they had accumulated, and to make them the target of uses and abuses. The work tries to penetrate into daily life in the villages, which had been transformed into small towns and places, through the Indians Directory. It also tries to analyze how social actors who took part in this new social reality experienced it, and to recover the origins of the laymen proprietary elite in the Grao Para, which had become empowered by the Jesuits banishing, as well as its business, and its compartment, after the Portuguese troops left the captaincy and conquered and settled in Caiena